Electrical Properties and AC Conductivity of (Bi0.5Na0.5)0.94Ba0.06TiO3 Ceramic. (15th October 2012) - Roy, Ansu K.; Singh, Amrita; Kumari, Karishma; Amar Nath, K.; Prasad, Ashutosh; Prasad, K.
Abstract : Lead-free perovskite (Bi0.5 Na0.5 )0.94 Ba0.06 TiO3 (BNBT06) was prepared by conventional ceramic fabrication technique at 1160°C/3h in air atmosphere. The crystal structure, microstructure, dielectric, polarization, piezoelectric properties, and ac conductivity of the sample were studied. X-ray diffraction data confirmed the formation of a single phase tetragonal unit cell. Williamson-Hall plot was used to calculate the lattice strain and the apparent particle size. The experimental relative density of BNBT06 was found to be 96-97% of the theoretical one with an average grain size 4 μ m. Room temperature dielectric constant and loss factor at 1 kHz were found to be equal to 781 and 0.085, respectively. Longitudinal piezoelectric charge coefficient of the poled sample under 2.5 kV/mm at 80°C in silicone bath was found to be equal to 124 pC/N. Complex impedance and electric modulus spectroscopic analyses showed the dielectric relaxation in the material to be of non-Debye type. The Nyquist plots and conductivity studies showed the NTCR character of BNBT06. The correlated barrier hopping model (CBHM) as well as jump relaxation model (JRM) was found to successfully explain the mechanism of charge transport in BNBT06. The ac conductivity data were used to evaluate the minimum hopping length, apparent activation energy, and density of states at Fermi level.